Remarks on the design and analyses of longitudinal studies for cancer patients with anorexia and weight loss - Le‐Rademacher, Jennifer G. (J Cachexia Sarcopenia Muscle, 2019)
Longitudinal data serve an important role in understanding the cancer anorexia weight loss syndrome and in testing interventions to palliative and treat patients who develop this syndrome. The element of time and the interrelatedness of data points define longitudinal data and add to the richness of this type of data. However, longitudinal data can also give rise to non‐random, missing data that can lead to flawed conclusions. This paper discusses these issues and suggests practical considerations for design and analysis of longitudinal cancer anorexia weight loss studies.